An exploration into the effect of COVID-19 on reward systems: A multiple case study - Klaas, Lusanda (Organisational Psychology, 2024)
The coronavirus (COVID-19) was declared as a pandemic in March 2020. To restrict the movement of the general population in order to reduce the transmission of COVID-19 a lockdown was implemented in more than 90 countries across the world. The lockdown was unpredictable and disrupted everyday life, leading to social and economic disruption. Socially, the lockdown has caused an increase in mental health disorders. Economically, it was predicted that the global economy would decrease and approximately 60 million individuals or more will end up living in extreme poverty. This is due to the abrupt change in normal business operations as organisations were forced to operate remotely. Therefore, to preserve their sustainability, organisations had to make important business-changing decisions such as layoffs, retrenchments, reducing employee and executive compensation, and possibly a revaluation of their reward systems. Using, the WorldatWork total rewards model as the theoretical framework, the objective of this qualitative research was to explore how COVID-19 shaped reward systems across organisations in different countries. An exploratory qualitative research design guided by the interpretivist paradigm was applied to this research study. Data was collected from a purposively selected sample of 12 participants through semi-structured one-on-one interviews. Using the Atlas.ti data analysis program, the key findings indicate that there were changes to each component of organisational reward systems